2001
DOI: 10.1542/peds.107.6.e102
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Autoimmune Markers in Children and Adolescents With Type 2 Diabetes

Abstract: ABSTRACT.Background. There is an increase in the incidence of type 2 diabetes in children and adolescents. Absence of known diabetes autoimmune markers is sometimes required to confirm the diagnosis.Objective. To identify clinical and autoimmune characteristics of type 2 diabetes in a pediatric population.Method. We report an analysis of 48 children and adolescents with type 2 diabetes, compared with 39 randomly selected children with type 1 diabetes, diagnosed and followed at the Loma Linda University Pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 21 publications
1
100
2
1
Order By: Relevance
“…In support of these findings, Hathout et al (40) evaluated the prevalence of islet cell antibodies and GAD and insulin AAs at clinical diagnosis of type 2 diabetes in a group of white and Hispanic children and adolescents. They found that none of the Hispanic children with type 2 diabetes exhibited signs of humoral islet cell autoimmunity.…”
Section: Discussionmentioning
confidence: 93%
“…In support of these findings, Hathout et al (40) evaluated the prevalence of islet cell antibodies and GAD and insulin AAs at clinical diagnosis of type 2 diabetes in a group of white and Hispanic children and adolescents. They found that none of the Hispanic children with type 2 diabetes exhibited signs of humoral islet cell autoimmunity.…”
Section: Discussionmentioning
confidence: 93%
“…Evidence for the coexistence of insulin resistance and insulin deficiency caused by autoimmune ␤-cell destruction was expanded in this population and proven by the performance of insulin-glucose clamps in a subset of subjects (24,25). A recent study from Hathout et al (26) found that among children and adolescents diagnosed with type 2 diabetes, almost 35% had at least one conventional AA. Case reports have also been published describing adolescents who present with features of both type 1 and type 2 diabetes (27).…”
Section: Follow-up Therapymentioning
confidence: 99%
“…Ö rtqvist et al (63) demonstrated independent correlations between age, sex, and ICA positivity with duration of partial remission. In a study of DAAs in children with clinical diagnosis of type 2 diabetes, all of the children who were ICA positive were on insulin therapy 1 year after diagnosis (64). In addition, in DAA ϩ adult diabetic patients, ICAs predict a decline in C-peptide (R.A. Jensen, L.K.G., C. Tö rn, M. Landin-Olsson, F.A.…”
Section: Do Autoantibodies Predict Clinical Course?mentioning
confidence: 99%